# Subtracting Algebraic Expression: Worksheets, Online Test and Calculators

Subtracting algebraic expression worksheets, solved worksheet problems or exercises with step-by-step work, formative assessment as online test, calculator and more learning resources to learn, practice, assess and master the basic math skills of algebra.

Subtracting Algebraic Expression
Name
Date

1
Sub 6x-5y-9z=4 and 4x-9y-5z=9
2
Sub 5x+10y=1 and 3x+4y=18
3
Sub 14y+5x=9 and 4y+3x=40
4
Sub 5x+12y=34 and 9x+2y=36
5
Sub 5m+6n-2p=19 and 4m+6n-p=40
6
Sub 6s+7t=2 and s+6t-12=0
7
Sub 10y+5z=1 and 2y+3z=23
8
Sub 4y+2x-2z=4 and 6x+9y-4z=7
9
Sub 9a+8b=0 and 6a+6b=-3
10
Sub -2x+2y+z=1 and 5x+3y+2z=7
11
Sub 2s-3t=2 and 5s-2t-12=0
12
Sub 12y-15z=19 and 12y+13z=30
13
Sub 14y+2x-12z=14 and 16x+9y-2z=17
14
Sub 9a+8b+c=20 and 6a+6b+2c=-3
15
Sub -12x+12y+3z=1 and 5x+13y+12z=70
16
Sub 3x+4y-5z=10 and 4x+5y-2z=20
17
Sub 3x+10y=1 and 13x+14y=18
18
Sub -14y+5x+8z=9 and -4y-3x+2z=40
19
Sub 15x+12y=34 and 19x+12y=36
20
Sub 15m-16n+3p=19 and 14m-16n+2p=0

Solved Worksheet Problems
Show All Workout
1
Sub 6x-5y-9z=4 and 4x-9y-5z=9
2x+4y-4z=-5
Solution
(6x-5y-9z=4) - ( 4x-9y-5z=9 )
Variable x terms are
(6x) - (4x)
= 2x

Variable y terms are
(-5y) - (-9y)
= 4y

Variable z terms are
(-9z) - (-5z)
= -4z

Constant  terms are
(4) - (9)
= -5

Hence the Equation is   2x+4y-4z=-5
2
Sub 5x+10y=1 and 3x+4y=18
2x+6y=-17
Solution
(5x+10y=1 ) - ( 3x+4y=18 )
Variable x terms are
(5x) - (3x)
= 2x

Variable y terms are
(10y) - (4y)
= 6y

Constant  terms are
(1) - (18)
= -17

Hence the Equation is   2x+6y=-17
3
Sub 14y+5x=9 and 4y+3x=40
10y+2x=-31
Solution
(14y+5x=9) - ( 4y+3x=40 )
Variable y terms are
(14y) - (4y)
= 10y

Variable x terms are
(5x) - (3x)
= 2x

Constant  terms are
(9) - (40)
= -31

Hence the Equation is   10y+2x=-31
4
Sub 5x+12y=34 and 9x+2y=36
-4x+10y=-2
Solution
(5x+12y=34) - ( 9x+2y=36 )
Variable x terms are
(5x) - (9x)
= -4x

Variable y terms are
(12y) - (2y)
= 10y

Constant  terms are
(34) - (36)
= -2

Hence the Equation is   -4x+10y=-2
5
Sub 5m+6n-2p=19 and 4m+6n-p=40
1m -1p=-21
Solution
(5m+6n-2p=19) - ( 4m+6n-p=40 )
Variable m terms are
(5m) - (4m)
= m

Variable n terms are
(6n) - (6n)
= 0

Variable p terms are
(-2p) - (-1p)
= -1p

Constant  terms are
(19) - (40)
= -21

Hence the Equation is   1m -1p=-21
6
Sub 6s+7t=2 and s+6t-12=0
5s+1t=-10
Solution
(6s+7t=2) - ( s+6t-12=0 )
Variable s terms are
(6s) - (1s)
= 5s

Variable t terms are
(7t) - (6t)
= t

Constant  terms are
(2) - (12)
= -10

Hence the Equation is   5s+1t=-10
7
Sub 10y+5z=1 and 2y+3z=23
8y+2z=-22
Solution
(10y+5z=1) - ( 2y+3z=23 )
Variable y terms are
(10y) - (2y)
= 8y

Variable z terms are
(5z) - (3z)
= 2z

Constant  terms are
(1) - (23)
= -22

Hence the Equation is   8y+2z=-22
8
Sub 4y+2x-2z=4 and 6x+9y-4z=7
-5y-4x+2z=-3
Solution
(4y+2x-2z=4) - ( 6x+9y-4z=7 )
Variable y terms are
(4y) - (9y)
= -5y

Variable x terms are
(2x) - (6x)
= -4x

Variable z terms are
(-2z) - (-4z)
= 2z

Constant  terms are
(4) - (7)
= -3

Hence the Equation is   -5y-4x+2z=-3
9
Sub 9a+8b=0 and 6a+6b=-3
3a+2b=3
Solution
(9a+8b=0) - ( 6a+6b=-3 )
Variable a terms are
(9a) - (6a)
= 3a

Variable b terms are
(8b) - (6b)
= 2b

Constant  terms are
(0) - (-3)
= 3

Hence the Equation is   3a+2b=3
10
Sub -2x+2y+z=1 and 5x+3y+2z=7
-7x-1y-1z=-6
Solution
(-2x+2y+z=1) - ( 5x+3y+2z=7 )
Variable x terms are
(-2x) - (5x)
= -7x

Variable y terms are
(2y) - (3y)
= -1y

Variable z terms are
(1z) - (2z)
= -1z

Constant  terms are
(1) - (7)
= -6

Hence the Equation is   -7x-1y-1z=-6
11
Sub 2s-3t=2 and 5s-2t-12=0
-3s-1t=-10
Solution
(2s-3t=2) - ( 5s-2t-12=0 )
Variable s terms are
(2s) - (5s)
= -3s

Variable t terms are
(-3t) - (-2t)
= -1t

Constant  terms are
(2) - (12)
= -10

Hence the Equation is   -3s-1t=-10
12
Sub 12y-15z=19 and 12y+13z=30
-28z=-11
Solution
(12y-15z=19) - ( 12y+13z=30 )
Variable y terms are
(12y) - (12y)
= 0

Variable z terms are
(-15z) - (13z)
= -28z

Constant  terms are
(19) - (30)
= -11

Hence the Equation is   -28z=-11
13
Sub 14y+2x-12z=14 and 16x+9y-2z=17
5y-14x-10z=-3
Solution
(14y+2x-12z=14) - ( 16x+9y-2z=17 )
Variable y terms are
(14y) - (9y)
= 5y

Variable x terms are
(2x) - (16x)
= -14x

Variable z terms are
(-12z) - (-2z)
= -10z

Constant  terms are
(14) - (17)
= -3

Hence the Equation is   5y-14x-10z=-3
14
Sub 9a+8b+c=20 and 6a+6b+2c=-3
3a+2b-1c=23
Solution
(9a+8b+c=20) - ( 6a+6b+2c=-3 )
Variable a terms are
(9a) - (6a)
= 3a

Variable b terms are
(8b) - (6b)
= 2b

Variable c terms are
(1c) - (2c)
= -1c

Constant  terms are
(20) - (-3)
= 23

Hence the Equation is   3a+2b-1c=23
15
Sub -12x+12y+3z=1 and 5x+13y+12z=70
-17x-1y-9z=-69
Solution
(-12x+12y+3z=1) - ( 5x+13y+12z=70 )
Variable x terms are
(-12x) - (5x)
= -17x

Variable y terms are
(12y) - (13y)
= -1y

Variable z terms are
(3z) - (12z)
= -9z

Constant  terms are
(1) - (70)
= -69

Hence the Equation is   -17x-1y-9z=-69
16
Sub 3x+4y-5z=10 and 4x+5y-2z=20
-1x-1y-3z=-10
Solution
(3x+4y-5z=10) - ( 4x+5y-2z=20 )
Variable x terms are
(3x) - (4x)
= -1x

Variable y terms are
(4y) - (5y)
= -1y

Variable z terms are
(-5z) - (-2z)
= -3z

Constant  terms are
(10) - (20)
= -10

Hence the Equation is   -1x-1y-3z=-10
17
Sub 3x+10y=1 and 13x+14y=18
-10x-4y=-17
Solution
(3x+10y=1 ) - ( 13x+14y=18 )
Variable x terms are
(3x) - (13x)
= -10x

Variable y terms are
(10y) - (14y)
= -4y

Constant  terms are
(1) - (18)
= -17

Hence the Equation is   -10x-4y=-17
18
Sub -14y+5x+8z=9 and -4y-3x+2z=40
-10y+8x+6z=-31
Solution
(-14y+5x+8z=9) - ( -4y-3x+2z=40 )
Variable y terms are
(-14y) - (-4y)
= -10y

Variable x terms are
(5x) - (-3x)
= 8x

Variable z terms are
(8z) - (2z)
= 6z

Constant  terms are
(9) - (40)
= -31

Hence the Equation is   -10y+8x+6z=-31
19
Sub 15x+12y=34 and 19x+12y=36
-4x =-2
Solution
(15x+12y=34) - ( 19x+12y=36 )
Variable x terms are
(15x) - (19x)
= -4x

Variable y terms are
(12y) - (12y)
= 0

Constant  terms are
(34) - (36)
= -2

Hence the Equation is   -4x =-2
20
Sub 15m-16n+3p=19 and 14m-16n+2p=0
1m +1p=19
Solution
(15m-16n+3p=19) - ( 14m-16n+2p=0 )
Variable m terms are
(15m) - (14m)
= m

Variable n terms are
(-16n) - (-16n)
= 0

Variable p terms are
(3p) - (2p)
= p

Constant  terms are
(19) - (0)
= 19

Hence the Equation is   1m +1p=19

## Worksheet: Subtracting Algebraic Expression

Subtracting algebraic expression worksheet is the largest collection of practice problems and solved exercises which can be served as homework, classwork or assignment problems for the students to learn, practice, assess, iterate and master the skills of how to solve such algebra problems in basic mathematics.

Online Test
00:00
Start my Challenge
Sub 9p-4q=9 and 3p-3q=4
Sub 4p+5q=5 and 5p+5q=4
Sub 4y+x-6z=8 and y+4x-6z=6
Sub m+2n=7 and m+7n=6
Sub 3x-5y=3 and 6x-6y=5
Sub x+8y=6 and x+6y=8
Sub m+10n=10 and m+10n=10
Sub p+6q=10 and p+10q=5
Sub 4p+3q=6 and 3p+6q=4
Sub 7x-2y=7 and 7x-7y=7

## Online Test: Subtracting Algebraic Expression

This online test to find the subtracting algebraic expression is a formative assessment which can be used as homework, classwork or assignment problems to assess and improve the learner's math skills on algebra.